Writing history in Portugal before 1200. Issue 2 (15th March 2021) - Furtado, Rodrigo
ABSTRACT: The writing of history, in medieval Latin, in the territory today known as Portugal, has been poorly studied. For the period before 1200, critical editions, comprehensive studies, even a list of known texts are lacking. Further, there has been no attempt to understand the Latin historiography of Portugal in its proper Iberian context. This paper seeks to address these issues. Focusing on the lands that would, during the twelfth century, evolve from the county of Portucale into the kingdom of Portugal up to the beginning of the thirteenth century, the paper establishes the historiographic sub-genres employed in the period; identifies the texts that were held in north-western Iberian libraries as possible sources or models for new texts; and presents an annotated catalogue of all known historiographical texts produced in the region.